Line mixing and broadening of carbon dioxide by argon in the v3 bandhead near 4.2 µm at high temperatures and high pressures. (September 2020) - Lee, Daniel D.; Bendana, Fabio A.; Nair, Anil P.; Pineda, Daniel I.; Spearrin, R. Mitchell
Highlights: CO2 Ar broadening parameters empirically determined for transitions J" = 99–145. A modified exponential gap law implement ed to model collisional line mixing. Thermodynamic scaling of collisional effects examined up to 3000 K and 58 atm. Abstract: Temperature-dependent line mixing and line broadening parameters were empirically-determined for rovibrational transitions ( J = 99–145) in the (00 0 0 → 00 0 1) and (01 1 0 → 01 1 1) bandheads of carbon dioxide near 4.2 µm. Collisional effects by argon on the high rotational energy lines ( E ″ = 3920–8090 cm − 1 ) in the R-branch were studied over a range of temperatures from 1200–3000 K in a shock tube. Measured absorption spectra comprising the target lines in an argon bath gas at near-atmospheric pressures were fit with Voigt profiles to determine line-broadening coefficients, with temperature dependence accounted by a power law. With line broadening established, line-mixing effects were examined at elevated pressures up to 58 atm and similar temperatures, reflecting conditions in high-pressure combustion environments. A modified exponential gap model for line mixing was developed to capture the pressure and temperature dependence of collisional transfer rates for the bandhead region using the relaxation matrix formalism.